Eschweilera brevipetiolata and E. silverstonei: Two new species of Lecythidaceae from western Colombia - Cornejo, Xavier (Phytotaxa, 2023)
Eschweilera brevipetiolata and E. silverstonei, two new species of Lecythidaceae known from the pluvial Chocoan forests of western Colombia, are described. Eschweilera brevipetiolata and E. silverstonei both occur in the Bajo Calima area, between 50–100 m elevation, in the department of Valle del Cauca. The new species are illustrated and their relationships with related species are discussed.